Development of Arabic Text Translation Teaching Materials For Students At Al-Fauzan Islamic Boarding School Lumajang - Achmad Syaifuji; Ita Nur Istiqomah; Ihya' Ulumuddin (Journal of Arabic Language Teaching, 2022)
The background of the research at the Al Fauzan Islamic Boarding School Lumajang is related to the ability of students who are still relatively lacking in translating Arabic texts. This problem occurs due to many reasons including a lack of enthusiasm in the learning. Likewise, the learning method is limited to listening to the teacher's explanation then students come forward to read and translate the book. The method used by the researcher is the Research and Development (R&D). The results of data analysis are as follows: 1) product specifications include book form, book content, translation, and evaluation 2) Validation of the development of translation teaching materials, namely validation of content validators and design validators 3) The effectiveness of developing speaking skills learning media is known through the SPSS application, where the data entry of the ' pre-test and post-test students to determine production efficiency, the researcher chose a test with the type of Sample Paired Test which has a basic formula, if the value of sig. 2-tailed less than 0.05 means indicating a significant difference between pre-test and post-test. Meanwhile, the data obtained by the researcher was 0.00, indicating that the value of sig. 2-tailed less than 0.05. So that student learning outcomes showed significant positive changes after using the developed product, namely in the form of translation teaching materials for Arabic texts at the Al Fauzan Islamic Boarding School Lumajang. خلفية البحث في معهد الفوزان الإسلامي لوماجانج لايزال كفاءة الطلبة في ترجمة النصوص العربية قليلة. هناك مشكلات في قلة تأهل الطلبة في كفاءة الترجمة للنصوص العربية. ظهرت هذة المشكلات بأسباب مختلفة منها عدم الحماسة للمطالعة بتعليمهم. كذلك في طريقة التدريس وهي تعتمد على الإستماع بشرح المدرس ثم يتقدم كل الطلبة لقراءتها وترجمتها. المنهج المستخدم الذي قام به الباحث في هذا البحث هو المنهج التطويري بنموذج Borg And Gall . نتائج تحليل البيانات كما تلي: 1) أما مواصفات الإنتاج فهي شكل الكتاب، مضمون الكتاب، الترجمة، التقويم 2) صلاحية تطوير مواد تعليم الترجمة للنصوص العربية هو من قبل صلاحية خبير المواد وخبير التصميم 3)أما فعالية الإنتاج فهي تعرف فعالية تطوير الإنتاج من خلال تطبيق SPSS ، حيث يتم فحص إدخال البيانات الخاصة بنتائج الاختبار القبلي والبعدي للطلبة. لمعرفة فاعلية الإنتاج ، اختارت الباحثة اختبارًا بنوع الاختبار Sampel Paired Test الذي له الصيغة الأساسية، إذا كانت قيمة sig. 2-tailed أصغر من 0.05 ، وهذا يدل على الفرق الكبير بين الاختبار القبلي والبعدي. بينما كانت البيانات التي حصلت عليها الباحثة 0.00 ، مما يدل على أن قيمة sig. 2-tailed أصغر من 0.05. تظهر نتائج تعليم الطلبة تغييرا إيجابيا كبيرا بعد استخدام الإنتاج التطويري أي كتاب الترجمة للنصوص العربية.